Gynecologic Cancer InterGroup (GCIG) Consensus Review for Small Cell Carcinoma of the Cervix. (1st November 2014) - Satoh, Toyomi; Takei, Yuji; Treilleux, Isabelle; Devouassoux-Shisheboran, Mojgan; Ledermann, Jonathan; Viswanathan, Akila N.; Mahner, Sven; Provencher, Diane M.; Mileshkin, Linda; Åvall-Lundqvist, Elizabeth; Pautier, Patricia; Reed, Nicholas Simon; et al.
Abstract : Abstract: Small cell carcinoma of the cervix (SCCC) is a rare histological entity of uterine cervical cancer. Compared with other common histological types, squamous cell carcinoma or adenocarcinoma, the outcome of SCCC is poor because of the high incidence of nodal or distant metastasis even with early stage. In this review, current consensus of epidemiology, pathology, and initial treatment for SCCC will be discussed.